Koncerti Filharmonične družbe med letoma 1794 in 1872 - Železnik, Sara (Muzikološki zbornik, 2011)
The article tries to create a picture of concert seasons of the Philharmonic Society in Ljubljana in accordance with the remaining concert programmes between the years 1794 and 1872. Individual studies have established the undisputable importance of the Society during the discussed period.
Keywords: 19.st.; 19th century; concert programmes; Filharmonična družba; koncertni sporedi; Philharmonic Society